THYROTOXIC CARDIOMYOPATHY MANIFESTING AS HEART FAILURE WITH SUPRANORMAL EJECTION FRACTION: A CASE REPORT - Hoàng Lưu, Tạ; Thắng Nam, Tạ; Võ Trí Dũng, Trần; Quốc Phòng, Nguyễn; Thị Kim Ngọc, Nguyễn; Thảo Uyên, Võ; Hữu Chí, Trần; Thanh Vy, Trần; Thanh Huân, Nguyễn (Journal of Health and Aging, 2026)
Thyrotoxic cardiomyopathy is categorized within the spectrum of metabolic cardiomyopathies and typically presents with high-output heart failure accompanied by a supranormal left ventricular ejection fraction. In recent years, heart failure with supranormal ejection fraction (HFsnEF) has been increasingly regarded as a distinct heart failure phenotype, exhibiting worse prognosis and suboptimal treatment response compared with the group with preserved ejection fraction. In this report, we present a clinical case of a patient admitted with fatigue, palpitations, and diarrhea. After comprehensive integration of clinical findings, laboratory test results, and imaging data, the patient was ultimately diagnosed with thyrotoxicosis accompanied by heart failure with supranormal ejection fraction. The patient was treated with a combination of antithyroid medication and a beta-blocker. After seven days of therapy, the patient demonstrated marked improvement in clinical symptoms as well as cardiac function on echocardiographic assessment.